PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN MENGGUNAKAN TOBINS’Q - Hermawan Sulistiyanto; Mirna Dyah Praptitorini S (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2016)
The purposeof this study was to find empirical evidence of theinfluence of company'sinvestment decision, financing decision, ,firmprofitability, firmproductivity and firmliquidity to the company’s value.Thestudy took a sample of mining and service mining companies listed inIndonesia Stock Exchange period of 2008 until 2012. Sampling wascollected by using purposive sampling technique. Samples obtained in thisstudy were 75 companies.The result of this research shows that investmentdecision and financing decision doesn’t have influence to firm value.But firmprofitability, firm productivity, and firm liquidity has positive influence tofirm value.